Enhanced perpendicular magnetocrystalline anisotropy energy in an artificial magnetic material with bulk spin-momentum coupling - Pradipto, Abdul-Muizz; Yakushiji, Kay; Ham, Woo Seung; Kim, Sanghoon; Shiota, Yoichi; Moriyama, Takahiro; Kim, Kyoung-Whan; Lee, Hyun-Woo; Nakamura, Kohji; Lee, Kyung-Jin; Ono, Teruo (AMER PHYSICAL SOC, 2019)
We systematically investigate the perpendicular magnetocrystalline anisotropy (MCA) in Co-Pt/Pd-based multilayers. Our magnetic measurement data show that the asymmetric Co/Pd/Pt multilayer has a significantly larger perpendicular magnetic anisotropy (PMA) energy compared to the symmetric Co/Pt and Co/Pd multilayer samples. We further support this experiment by first-principles calculations on CoPt2, CoPd2, and CoPtPd, which are composite bulk materials that consist of three atomic layers in a unit cell, Pt/Co/Pt, Pd/Co/Pd, and Pt/Co/Pd, respectively. By estimating the contribution of bulk spin-momentum coupling to the MCA energy, we show that the CoPtPd multilayer with symmetry breaking has a significantly larger PMA energy than the other multilayers that are otherwise similar but lack symmetry breaking. This observation thus provides evidence of the PMA enhancement due to the structural inversion symmetry breaking and highlights the asymmetric CoPtPd as an artificial magnetic material with bulk spin-momentum coupling, which opens a pathway toward the design of materials with strong PMA.
Keywords: ELECTRIC-FIELD CONTROL; MICROSCOPIC ORIGIN; ELECTRONICS; SURFACES; CO/PT